Atrial flutter without structural heart disease in pediatrics: a retrospective review of cases in the Hospital Infantil Miguel Servet, Zaragoza, Spain - Tamara Moliner-Morón; Rebeca Santiago-Cortés; Ariadna Ayerza-Casas; Marcos Clavero-Adell; Lorenzo Jiménez-Montañés; Daniel Palanca-Arias (Boletín Médico del Hospital Infantil de México, 2022)
Background: Atrial flutter is a rare condition in pediatrics that usually occurs as a late complication after surgery for congenital heart diseases, although it can also appear in structurally normal hearts. Clinical cases: We conducted a retrospective study of cases of atrial flutter with no structural heart disease diagnosed in a pediatric population (between 0 and 15 years of age) during 2015-2021 in a tertiary hospital. A total of seven cases were diagnosed, with a clear predominance of males (6/7). Of the seven patients, five debuted in the perinatal period: two were diagnosed at 20 and 36 hours of life, and three, prenatally. Among these perinatal cases, more than half (3/5) were preterm. The treatment was electrical cardioversion. The evolution was satisfactory in these cases, and there were no tachycardias in their subsequent development. In contrast, when the debut occurred at a later age (5-7 years), it was associated with channelopathy (Brugada syndrome and catecholaminergic polymorphic ventricular tachycardia), and electrical ablation of the ectopic focus was required due to poor response to pharmacological treatment. Conclusions: This study confirms the low incidence of this pathology in pediatrics and the benignity and good prognosis of neonatal flutter in most cases. The prognosis worsens when atrial flutter is diagnosed in older children, and the probability of concomitant associated heart disease increases.